Treatable mortality and health care related factors across European countries - Tavares, Aida Isabel (Frontiers in Public Health, 2024)
Introduction: Despite the improvements in European health systems, a large number of premature deaths are attributable to treatable mortality. Men make up the majority of these deaths, with a significant gap existing between women and men's treatable mortality rate in the EU.Aim: This study aims to identify the healthcare-related factors, including health expenditures, human and physical resources, and hospital services use associated with treatable mortality in women and men across European countries during the period 2011-2019.Methods: We use Eurostat data for 28 EU countries in the period 2011-2019. We estimate a panel data linear regression with country fixed effects and quantile linear regression for men and women. Results: The results found i) differences in drivers for male and female treatable mortality, but common drivers hold the same direction for both sexes; ii) favorable drivers are GDP per capita, health expenditures, number of physicians per capita, and (only for men) the average length of a hospital stay, iii) unfavorable drivers are nurses and beds per capita, although nurses are not significant for explaining female mortality.Conclusion: Policy recommendations may arise that involve an improvement in hospital bed management and the design of more specific policies aimed at healthcare professionals.